2021
DOI: 10.36560/14820211430
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas de amora-preta ‘Tupy’ colhidas em diferentes estádios de maturação e mantidas sob refrigeração

Abstract: A qualidade e a conservação pós-colheita da amora-preta está diretamente relacionadas ao estádio de maturação em que são colhidas. Muitos produtores tem colhido fora do ponto ideal de colheita para comercialização e consumo. O objetivo deste trabalho foi avaliar a qualidade físico-química de amoras-pretas ‘Tupy’ sob armazenamento refrigerado, colhidas em diferentes estádios de maturação. Amoras provenientes de um pomar do campo experimental pertencente à Embrapa Clima Temperado, Pelotas-RS, foram colhidas em t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…et al (2022) UV-C radiation in postharvest quality of... Mass loss influences fruit appearance, which can cause consumer rejection due to the wilting condition(Schiavon et al, 2021), a fact that was not observed in this study, which presented very low losses (below 0.5%), demonstrating that all treatments were efficient in conserving this parameter.Red dragon fruits submitted to different UV-C radiation doses were evaluated after the 16th day regarding postharvest conservation at 1-day intervals and fruits from all treatments remained stable and with conditions of commercialization and consumption for up to 21 days based on their external visual appearance.The fruits showed a dark coloring of the peel from the 22nd day of storage, with the appearance of apparent signs of deterioration, such as fermentation of the peel's tissues, although the pulp was internally intact Istianingsih & Efendi (2013). preserved dragon fruits (Hylocereus costaricensis) for 14 days stored at 15 °C and found a shorter shelf life than that verified in this study.…”
mentioning
confidence: 51%
“…et al (2022) UV-C radiation in postharvest quality of... Mass loss influences fruit appearance, which can cause consumer rejection due to the wilting condition(Schiavon et al, 2021), a fact that was not observed in this study, which presented very low losses (below 0.5%), demonstrating that all treatments were efficient in conserving this parameter.Red dragon fruits submitted to different UV-C radiation doses were evaluated after the 16th day regarding postharvest conservation at 1-day intervals and fruits from all treatments remained stable and with conditions of commercialization and consumption for up to 21 days based on their external visual appearance.The fruits showed a dark coloring of the peel from the 22nd day of storage, with the appearance of apparent signs of deterioration, such as fermentation of the peel's tissues, although the pulp was internally intact Istianingsih & Efendi (2013). preserved dragon fruits (Hylocereus costaricensis) for 14 days stored at 15 °C and found a shorter shelf life than that verified in this study.…”
mentioning
confidence: 51%
“…A partir dessa variável, obtém-se a cor real do objeto analisado, onde os maiores valores de croma apresentam cores mais vivas (Siqueira, 2012). Ela representa a saturação das cores, quanto maior o valor, mais pura é a cor (Schiavon et al, 2021). A geleia de murta apresentou valor de 12,52 para esse parâmetro, sendo esse um valor relativamente baixo, indicando que o produto, após o processamento, apresentou cor mais opaca.…”
Section: Parâmetrosunclassified